Increase in fine root biomass enhances root exudation by long-term soil warming in a temperate forest - Heinzle, Jakob; Liu, Xiaofei; Tian, Ye; Kwatcho Kengdo, Steve; Heinze, Berthold; Nirschi, Annika; Borken, Werner; Inselsbacher, Erich; Wanek, Wolfgang; Schindlbacher, Andreas (Frontiers in Forests and Global Change, 2023)
Trees can invest up to one-third of the carbon (C) fixed by photosynthesis into belowground allocation, including fine root exudation into the rhizosphere. It is still unclear how climate and soil warming affect tree root C exudation, in particular quantifying longer-term warming effects remains a challenge. In this study, using a C-free cuvette incubation method, in situ C exudation rates from tree fine roots of a mature spruce dominated temperate forest were measured in regular intervals during the 14th and 15th year of experimental soil warming (+ 4°C). In addition, a short-term temperature sensitivity experiment (up to + 10°C warming within 4 days) was conducted to determine the inherent temperature sensitivity of root exudation. Root exudation rates in the long-term warmed soil (17.9 μg C g–1 root biomass h–1) did not differ from those in untreated soil (16.2 μg C g–1 root biomass h–1). However, a clear increase (Q10 ∼5.0) during the short-term temperature sensitivity experiment suggested that fine root exudation can be affected by short-term changes in soil temperature. The absence of response in long-term warmed soils suggests a downregulation of C exudation from the individual fine roots in the warmed soils. The lack of any relationship between exudation rates and the seasonal temperature course, further suggests that plant phenology and plant C allocation dynamics have more influence on seasonal changes in fine root C exudation. Although exudation rates per g dry mass of fine roots were only marginally higher in the warmed soil, total fine root C exudation per m2 soil surface area increased by ∼30% from 0.33 to 0.43 Mg C ha–1 yr–1 because long-term soil warming has led to an increase in total fine root biomass. Mineralization of additional fine root exudates could have added to the sustained increase in soil CO2 efflux from the warmed forest soil at the experimental site.